Word play : experimental poetry and Soviet children's literature - Morse, Ainsley (Studies in Russian literature and theory., 2021)
"Word Play focuses on the intertwined fates of children's literature and underground poetry throughout the Soviet period. Five case studies feature experimental poets whose unpublished work was not written for children but featured a childlike lyric speaker, diction, form, and humor"--